On the Interaction between Fear and Hatred - Syed Mansoob Murshed (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper models conflictual interaction between a European state and a domestic dissident immigrant minority group, Muslims say, some of whom may resort to acts of terrorism. Here, identity is crucial and provides the micro-foundations of dissident behaviour by solving the collective action problem; however, complex multiple identities are possible. Militancy or hatred of the West arises both because of the economic and social disadvantage experienced by Muslims or horizontal inequalities, as well as historical grievances and contemporary foreign policy actions that discriminate against the Muslim world. The fear of visible Muslim minorities among the European host population may be a product of strident propaganda emanating from certain segments of Western society. The innovation of the paper lies in modelling the interaction between fear and hatred. Excessive deterrence against 'dangerous' minority groups may backfire, compared to more accommodative policies. Space needs to be created so that Muslim migrants are able to merge their personal identities within their adopted European homelands. Also, the economic disadvantage experienced by Muslims needs redressing.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: C72; D74; D81; H11; 330; European Security; Conflict; Terrorism